Komparasi Pelaksanaan Supervisi Akademik Kepala Sekolah di SMKN 1 Padang Gelugur dengan SMKN 1 Rao Selatan - Vovi Tridian Ulfah; Yulianto Santoso; Rifma Rifma; Ermita Ermita (Journal of Educational Administration and Leadership, 2021)
Academic Supervision is a series of activities to assist in developing teacher professionalism in the implementation of learning with students carried out by leaders in schools, namely the principal. Academic supervision activities are carried out to help teachers improve learning activity planning, learning implementation, learning evaluation, and learning device preparation. This study aims to determine the implementation of the principal's academic supervision and see whether there is a significant difference in the implementation of the principal's academic supervision at SMKN 1 Padang Gelugur with SMKN 1 Rao selatan. This type of research is comparative descriptive and data collection is done by distributing questionnaires that have been tested for their validity and reliability. Before the data were analyzed, the data had been tested for normality and homogeneity and then performed the t-test to determine the difference value. Acquisition of data analysis is 1) academic supervision planning obtained 82.27% with the effective category. 2) the implementation of academic supervision obtained 79.34 in the quite effective category. 3) feedback and follow-up from the results of academic supervision obtained 75.2% including in the quite effective category. After testing the hypothesis using the SPSS application, namely the t-test, the result was that there was a difference in the implementation of the principal's academic supervision at SMKN 1 Padang Gelugur and SMKN 1 Rao Selatan because t count (2.154) <from t table (2.66). Based on the research results, the implementation of the principal's academic supervision at SMKN 1 Padang Gelugur was 1.08% more effective than SMKN 1 Rao Selatan.